Measuring the performance of health care services: a review of international experiences and their application to urban contexts Medir el desempeño de los servicios de salud: revisión de las experiencias internacionales y su aplicación a contextos urbanos - Anna García-Altés; Lauriane Zonco; Carme Borrell; Antoni Plasència (Elsevier, 2006)
Background: The objective of performance assessment is to provide governments and populations with appropriate information about the state of their health care system. The objective of this paper is to present the most recent developments in performance assessment and their application in urban contexts. Methods: Literature review in PubMed (1970-2004). We identified additional papers and grey literature from retrieved references. Results: Performance assessment initiatives were identified in Australia, Canada, the United Kingdom, and New Zealand. The World Health Report 2000 is one of the best known examples of a transnational approach to performance assessment. Conclusion: The best developed initiatives to date are those that define precise categories, criteria and indicators with which to analyse and assess health care systems, based on a solid conceptual framework. Performance assessment fits perfectly in urban contexts, as it is a useful tool for designing and monitoring policies, assessing the quality of the services provided, and measuring the health status of city dwellers. Barcelona and Montreal are currently collaborating together on a project to assess the performance assessment of their respective health care services. Objetivos: El objetivo de la evaluación del desempeño es dar información apropiada a los gobiernos y las poblaciones sobre el funcionamiento de su sistema sanitario. El objetivo de este artículo es presentar los desarrollos más recientes en la medida del desempeño y su aplicación en contextos urbanos. Métodos: Revisión de la bibliografía en PubMed (1970-2004). Se identificaron artículos adicionales y bibliografía gris y de las referencias de los artículos seleccionados. Resultados: Se identificaron iniciativas de medida del desempeño en Australia, Canadá, Reino Unido y Nueva Zelanda. La iniciativa transnacional del Informe sobre la salud en el mundo 2000 de la Organización Mundial de la Salud (OMS) es una de las más conocidas. Conclusiones: Las iniciativas más desarrolladas en la actualidad son las que definen categorías, criterios e indicadores para analizar y evaluar los sistemas sanitarios, basándose en un marco conceptual sólido. La medida del desempeño encaja perfectamente en los contextos urbanos, ya que es una herramienta útil para diseñar y hacer un seguimiento del nivel de consecución de las políticas en marcha, medir la calidad de los servicios disponibles y el estado de salud de los habitantes de una población. Barcelona y Montreal están trabajando en un proyecto de colaboración para la evaluación del desempeño de sus servicios sanitarios.